Manajemen Pelayanan Bimbingan dan Konseling Melalui Website di Madrasah Tsanawiyah Negeri 8 Jember - Erna Dwi Lestari; Nur Ittihadatul Ummah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze and develop the management of guidance and counseling (GC) services through a website at Madrasah Tsanawiyah Negeri (MTsN) 8 Jember. The primary focus is to understand the implementation of web-based systems to support GC services, improve communication efficiency among counselors, students, and parents, and systematically document service outcomes. The research employed a qualitative descriptive method with data collected through interviews, observations, and documentation. The findings reveal that the website as a medium for GC services accelerates the information delivery process, facilitates students in accessing counseling services, and increases parental participation. Additionally, the system supports structured data management, making service evaluation more efficient. With proper management, the website becomes an effective tool in achieving GC objectives at MTsN 8 Jember.